RECOMMENDATIONS FOR PAIN RELIEF IN LABOR - Eduarda Almeida de Souza, Cicera; Cavalcante de Sá Florêncio, Patrícia; Cesar Pereira da Silva, Julio; Melo Moreira, Leticia; Guiomar da Silva, Regineide; Lima da Silva, Nathalia; Comassetto, Isabel; Silva Ferreira, Andreia; Luiz Fidelis de Lima, André (Health and Society, 2023)
Introduction: Childbirth is considered a painful experience for women, since, during the uterine contraction phases, pain can be felt at different stages and can arise from many different places. Pain happens at the beginning of uterine contractions, gradually increasing and lasting longer. When contractions happen more frequently, pain may arise within 3 to 5 minutes. In view of this, humanization in the obstetric sector stands out as one of the main recommendations imposed by the Ministry of Health, in order to provide adequate follow-up under dignified conditions for the patient. In view of this, this research will address alternative treatment options that can help minimize pain during labor. Objective: To show, through the scientific literature, the main recommendations for pain relief during labor. Methodology: This research was carried out through an integrative literature review, with an exploratory approach, whose institute was summarized in investigating, through already published articles, relevant information that answered the guiding question. The searches took place in the scientific databases: LILACS, SCIELO and MEDLINE. Results and Discussion: Thus, the results show that, before resorting to analgesia, for pain relief, it is important to opt for the use of non-pharmacological alternative methods, natural sources that are not drugs, can be used to relieve pain. of childbirth. There are several techniques to reduce women’s suffering by working with their psycho-emotional and spiritual aspects. Allied to this, childbirth education reduces women’s anxiety, allows for a more positive attitude during labor, increases women’s satisfaction with childbirth, reduces the need for anesthesia, increases the likelihood of vaginal delivery, and increases chances of having a difficult birth. bringing parents and babies together and bringing a sense of accomplishment during childbirth. birthday. Conclusion: Through data collection, it can be seen the need to expand research on the subject, disseminate information about its effectiveness and benefits to professionals who provide obstetric services, encourage the introduction of non-pharmacological methods in clinical practice by professionals of health and encourage institutions to support midwifery services and disseminate information on how to incorporate this practice into their routine.